Global variation in the long-term outcomes of ypT0 rectal cancers. Issue 3 (March 2020) - Lorenzon, Laura; Evrard, Serge; Beets, Geerard; Gonzalez-Moreno, Santiago; Kovacs, Tibor; D'Ugo, Domenico; Polom, Karol
Abstract: Background: Colorectal cancer mortality presents world-wide variation. In rectal cancers presenting a complete/nearly-complete tumor response (ypT0/ypTis) following neoadjuvant treatment, the features correlated to nodal metastases and relapses still need to be defined. Methods: An international cohort study enrolling ypT0/ypTis rectal cancers surgically treated from 2012 to 2017 was conducted. A propensity matching was used to balance nodal-positive and nodal-negative patients and statistical analyses were performed to investigate survivals, using a bootstrap model for internal validation. The features correlated with nodal metastasis were studied. Countries with participating centers were ranked using the World Bank (WBI), Human Development (HDI) and Global Gender Gap (GGG) indexes to compare survivals. Results: 680 ypT0/ypTis from 52 European, Australian, Indian and American Institutions were analyzed. Mean follow-up was of 30.4 months. 96.5% were treated with total mesorectal excision, 7.2% were nodal-positive and 8.8% relapsed. Distal cancers (HR 0.71 95%CI: 0.56-0.91) and nodal metastasis and nodal metastasis (HR 3.85 95%CI:1.12–13.19) correlated with worse DFS, whereas a younger age was of borderline significance (HR 0.95 95%CI:0.91–0.99). The bootstrap analysis validated the model on 5000 repetitions. A short-course radiotherapy (OR 0.18 95%CI:0.09–0.37) correlated with the occurrence of nodal metastasis. Those countries classified in the low/medium-WBI, medium-HDI and lower-GGG ranks documented worse DFS curves (respectively p < 0.0001, p < 0.0001 and p 0.0002). However, the clinical stages were similar and patients from medium-HDI countries received more adjuvant chemotherapy than the others (p < 0.0001). Conclusion: Sub-groups at risk for relapses and nodal metastasis were identified. A global variation exists also when benchmarking a rectal cancer complete regression.